Availability of antiepileptic drugs across Europe. (19th October 2015) - Baftiu, Arton; Johannessen Landmark, Cecilie; Nikaj, Valent; Neslein, Inger‐Lise; Johannessen, Svein I.; Perucca, Emilio
Summary: Europe consists of 53 countries with widely different economic conditions and different political, educational, and health care systems. This study was aimed at determining the availability of antiepileptic drugs (AEDs) across Europe. An electronic questionnaire was submitted to all 43 European chapters of the International League Against Epilepsy (ILAE). Outcome measures were availability of older, newer, and newest AEDs, generic products, indications, reimbursement rules, and reasons for lack of availability of AEDs. Countries were divided according to economic status as defined by the World Bank. Thirty‐four chapters (79%) provided data. There were large differences in AED availability across countries, especially between high‐income countries and the other countries. The newest AEDs were not available in any of the 12 non–high‐income countries. Availability was higher in countries with public reimbursement systems. Reimbursement policies ranged from full reimbursement for all AEDs to complete lack of reimbursement. Main hurdles for poor access to AEDs included lack of regulatory approval, high prices and reimbursement restrictions. The availability of AEDs differs across European countries, with many hurdles hampering access to epilepsy medicines, particularly to new medications. These findings raise major concerns on the quality of epilepsy care in many countries.